Aplysin Protects Against Alcohol‐Induced Liver Injury Via Alleviating Oxidative Damage and Modulating Endogenous Apoptosis‐Related Genes Expression in Rats. Issue 10 (7th September 2018) - Ge, Na; Liang, Hui; Zhao, Yuan‐yuan; Liu, Ying; Gong, An‐jing; Zhang, Wen‐long
Abstract : Abstract: We investigated the protective effects and possible mechanisms of Aplysin against alcohol‐induced liver injury. Rats were given daily either alcohol only (alcohol model group; 8 to 12 mL/kg body weight), one of three doses of Aplysin (50, 100, or 150 mg/kg Aplysin) plus alcohol, or volume‐matched saline. After 6 weeks, the effects of Aplysin were assessed in terms of changes in histology, biochemical indices, and DNA oxidative damage. Potential mechanisms were analyzed through measurements of lipid peroxidation, antioxidant defense systems, expression of cytochrome P450 2E1, and expression of apoptosis‐related genes. We found that Aplysin significantly protected the liver against alcohol‐induced oxidative injury, evidenced by improved hepatic histological structure, inhibited alcohol‐induced elevation of serum biochemical indices, attenuated extents of hepatocellular DNA damage. At a mechanistic level, Aplysin alleviated alcohol‐induced oxidative stress as illustrated by the revivification of erythrocyte membrane fluidity, the attenuation of glutathione depletion, the restoration of antioxidase activities, and reduced malondialdehyde overproduction. Furthermore, the mRNA levels of Bax, cytochrome c, and cytochrome P450 2E1 were significantly down‐regulated, whereas those of Bcl‐2 and caspase‐9 and caspase‐3 were markedly up‐regulated. These findings suggest that Aplysin provides significant protection against alcohol‐induced liver injury, possibly through alleviating oxidative damage and modulating endogenous apoptosis‐related genes expression. Practical Application: Many natural components derived from alga have been used in the food, cosmetics, and biomedicine industries. Aplysin, a marine bromosesquiterpene, was extracted from the red alga Laurencia tristicha, which could effectively protect against alcohol‐induced liver injury, might be a potential natural sources for preventing alcoholic liver damage.